Computer simulation of reinforced concrete columns confined with CFRP - Silva, Tiago Nobre da; Albuquerque, Carla Simone de; Real, Mauro de Vasconcellos; Suriano da Silva Júnior, Francisco Eudázio (International Journal of Advanced Engineering Research and Science, 2022)
Carbon Fiber Reinforced Polymer (CFRP) reinforcement of reinforced concrete (RC) columns has become increasingly common. This work presents a finite element computational model capable of representing the structural behavior of CFRP-confined square RC columns. Data and results from experimental research available in the literature are used to assess the ability of the proposed model to represent the test results. It is possible to observe that the models were able to represent, with adequate precision, the structural behavior of columns with different configurations of longitudinal reinforcement, stirrups spacing, number of CFRP layers, and type of load.